Wall Pressure Measurements Beneath the Supersonic Jets in an Abruptly Augmented Nozzle - Bashir, Musavir; Khan, Sher Afghan; Choudhary, Zakir Ilahi; Shinde, V. S. (akademia Baru, 2020)
The ballistic research has introduced the requirements for obtaining aerodynamic data including base and wall pressures over a very wide range of Mach number, Reynolds number, and manipulation of these forces by applying both active and passive control strategies. The manipulation of base and wall pressure plays a significant role in bluff body aerodynamics and control of aerodynamic forces is essential in the reduction of drag and improving the overall performance of such bodies. In this study, an experimental investigation was conducted in sudden expansion axis-symmetric passage for controlling wall pressure. Micro jets constituting four micro-holes around base and symmetric to nozzle axis are used as active control to manipulate the wall pressure. Wall pressure distribution is depicted for Mach numbers 1.25 and 1.3 respectively. Length-to-diameter (L/D) ratios of current investigation range from 10 to 5 with area ratios of 2.56. It is found that wall pressure is highly impacted by the microjet flow control at certain Mach numbers and geometrical parameters like the area ratio and L/D ratio also play a significant role in flow control and 50 % to 60% increase in the wall pressure is found at L/D = 10. It is also shown that the nozzle pressure ratio (NPR) also influences the wall pressure. However, the wall pressure distribution of the ducts is found fluctuating in nature in case of correctly expanded flows and remains ineffective even with microjet control.